Entrepreneurship, Leadership, and the Value of Feminist Approaches to Understanding Them. (17th April 2015) - Galloway, Laura; Kapasi, Isla; Sang, Katherine; Henry, Colette; Foss, Lene; Fayolle, Alain; Walker, Elizabeth; Duffy, Susan
<x xml:space="preserve">Abstract</x> Entrepreneurship research principally focuses on business growth. This focus valorizes the masculine and marginalizes other interpretations. Consequently, entrepreneurship is restricted to a phenomenon that is rare in the diverse business world. The leadership literature proposes that entrepreneurship may not be as masculine as we assume anyway. Our understanding of entrepreneurship needs development at the conceptual level. We argue that performativity, as described in feminist theory, can contribute to how we interpret entrepreneurship and that this might inform both the entrepreneurship and leadership literatures to afford us better understanding of what we might mean by "entrepreneurial leadership."